GIS tools for urban prospecting. Simulations aimed at revitalizing San José’s historic downtown as part of the San José RISE Project - Guevara-Murillo, Mauricio (2025)
Geographic information systems have evolved to facilitate cartographic representation processes and promote more objective and efficient analysis and decision-making processes. The use of GIS in Costa Rica’s urban planning is constantly growing, making it increasingly easier to access geographic information for territorial administration and management. However, this implementation is not standardized; each urban planning process depends directly on the technical capabilities of the institutions responsible for territorial administration and the data available in each case. As part of the research project “Real Estate Reactivation of the Historic Center of San José through Alternative Financing Platforms” (San José RISE), an urban assessment is being conducted to assess the current situation of San José’s historic center and define an action plan for the real estate rehabilitation of its building stock. This article proposes disseminating a scenario planning process developed using GIS tools, based on primary inputs gathered during the urban assessment. The objective was to identify potential zones and polygons for concentrating urban rehabilitation efforts. The exercises developed allowed mapping different areas of interest according to the priorities in objectives and strategies. While the use of GIS and automated geoprocessing enables the standardization and objectification of results, it is concluded that expert judgment is essential when defining variables in the analysis process. Therefore, although a working methodology has been established, the result will depend on both quantitative criteria supported by the GIS and qualitative elements that experts and technicians must assess.